2016
DOI: 10.1089/neu.2015.4262
|View full text |Cite
|
Sign up to set email alerts
|

Tau Oligomers Derived from Traumatic Brain Injury Cause Cognitive Impairment and Accelerate Onset of Pathology in Htau Mice

Abstract: Tau aggregation is a pathological feature of numerous neurodegenerative disorders and has also been shown to occur under certain conditions of traumatic brain injury (TBI). Currently, no effective treatments exist for the long-term effects of TBI. In some cases, TBI not only induces cognitive changes immediately post-injury, but also leads to increased incidence of neurodegeneration later in life. Growing evidence from our lab and others suggests that the oligomeric forms of tau initiate the onset and spread o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 52 publications
1
54
0
Order By: Relevance
“…Kondo and colleagues proposed that cis tau might play a role [27]. Kayed et al assert that it is more likely the tau oligomers [28]. We however have discovered an earlier contributor to the disease process in tau acetylation.…”
Section: Current Understanding Of Ctementioning
confidence: 54%
“…Kondo and colleagues proposed that cis tau might play a role [27]. Kayed et al assert that it is more likely the tau oligomers [28]. We however have discovered an earlier contributor to the disease process in tau acetylation.…”
Section: Current Understanding Of Ctementioning
confidence: 54%
“…Once tau is secreted, the extracellular tau has the ability to enhance tau pathology. For example, transplanting TBI induced tau oligomers into naive brains of hTau transgenic mice results in oligomeric spread of tau and accelerated cognitive impairment (Gerson et al , 2016), secreted tau fibrils are capable of inducing transcellular misfolding and tau aggregation (Kfoury et al , 2012), and hyperphosphorylated tau is capable of forming filaments and tangles with non-phosphorylated tau (Alonso et al , 1996). Therefore, it is possible that in non-familial tauopathies, such as CTE, an initial event, such as repetitive TBI, triggers a misfolding cascade which can then be transmitted in a prion-like manner (Morales et al , 2015).…”
Section: The Tau Protein – Functions and Dysfunctionsmentioning
confidence: 99%
“…CCI, a focal model of injury which includes aspects of contusion, hemorrhage and diffuse injury (Hall et al , 2005), results in severity-dependent increases in cleaved tau (c-tau), with severe injury inducing significant increases in c-tau beginning at 6h in the cortex and 48h in the hippocampus, increases which are sustained for at least seven days following injury and which are attenuated by the neuroprotective drug CsA (Gabbita et al , 2005). Similarly, following a moderate FPI, a mixed model of focal and diffuse injury (Thompson et al , 2005), oligomeric and phosphorylated tau are increased acutely: 4h, 24h and 2 weeks post-injury (Gerson et al , 2016; Hawkins et al , 2013). Mild blast TBI, which encompasses both the blast wave and rotational acceleration-deceleration forces and results in diffuse injury, transient axonal injury, and vascular pathology (Courtney and Courtney, 2015; Kovacs et al , 2014), has also been shown to increase tau acutely following injury.…”
Section: Tbi Tau and Cte - The Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations